Tracheal intubation in an urban emergency department in Scotland: A prospective, observational study of 3738 intubations. (April 2015) - Kerslake, Dean; Oglesby, Angela J.; Di Rollo, Nicola; James, Ed; McKeown, Dermot W.; Ray, David C.; ,
Abstract: Aim: The emergency department (ED) is an area where major airway difficulties can occur, often as complications of rapid sequence induction (RSI). We undertook a prospective, observational study of tracheal intubation performed in a large, urban UK ED to study this further. Methods: We reviewed data on every intubation attempt made in our ED between January 1999 and December 2011. We recorded techniques and drugs used, intubator details, success rate, and associated complications. Tracheal intubation in our ED is managed jointly by emergency physicians and anaesthetists; an anaesthetist is contacted to attend to support ED staff when RSI is being performed. Results: We included 3738 intubations in analysis. 2749 (74%) were RSIs, 361 (10%) were other drug combinations, and 628 (17%) received no drugs. Emergency physicians performed 78% and anaesthetists 22% of intubations. Tracheal intubation was successful in 3724 patients (99.6%). First time success rate was 85%; 98% of patients were successfully intubated with two or fewer attempts, and three patients (0.1%) had more than three attempts. Intubation failed in 14 patients; five (0.13%) had a surgical airway performed. Associated complications occurred in 286 (8%) patients. The incidence of complications was associated with the number of attempts made; 7% in one attempt, 15% in two attempts, and 32% in three attempts ( p < 0.001). Conclusion: A collaborative approach between emergency physicians and anaesthetists contributed to a high rate of successful intubation and a low rate of complications. Close collaboration in training and delivery of service models is essential to maintain these high standards and achieve further improvement where possible.